Relapse treatment with low-dose steroids in steroid-sensitive minimal change disease - Martin Capon, Irene; Gutierrez, Eduardo; Huerta, Ana; Viera, Elizabeth; Alvarez Nadal, Marta; Fernández-Lucas, Milagros; Villacorta, Javier (Frontiers in Nephrology, 2024)
BackgroundThe treatment of minimal change disease (MCD) consists of a high dose of steroids for several months, implying significant drug toxicity. Nevertheless, relapses of steroid-sensitive MCD usually respond to lower doses of steroids.MethodsThe objective of this study was to analyze whether a low dose of steroids (LDS) is effective for the treatment of MCD relapses. Since 2018, new relapses of steroid-sensitive adult patients with MCD in three Spanish centers have been treated with LDS. The cumulative dose of steroids, the time to remission, and the relapse-free time were compared between relapses treated with LDS and previous relapses of the same patients treated with a standard dose of steroids (SDS).ResultsA total of 51 relapses in 31 patients were treated with LDS and compared with 48 historical relapses of the same patients treated with SDS. The mean doses of prednisone adjusted by weight for the initial treatment were 0.45 mg/kg (0.40–0.51 mg/kg) in the relapses treated with LDS and 0.88 mg/kg (0.81–1.00 mg/kg) in those treated with SDS. The mean cumulative doses of prednisone in LDS- and SDS-treated relapses were 1,191 mg (801–1,890 mg) and 3,700 mg (2,755–5,800 mg), respectively. The duration of treatment was 63 days (42–117 days) in the LDS group and was 140 days (65–195 days) in the SDS group. All patients achieved complete remission within 1 month after steroid therapy in both groups. The times to remission of the LDS and SDS groups were 19.10 ± 12.80 and 18.93 ± 12.98 days, respectively (p = 0.95).ConclusionAmong the steroid-sensitive patients with MCD, relapse therapy with LDS (0.5 mg/kg) appears effective and allows minimization of the steroid cumulative dose.